Exact soliton of (2 + 1)-dimensional fractional Schrödinger equation. (July 2017) - Rizvi, S.T.R.; Ali, K.; Bashir, S.; Younis, M.; Ashraf, R.; Ahmad, M.O.
Abstract: The nonlinear fractional Schrödinger equation is the basic equation of fractional quantum mechanics introduced by Nick Laskin in 2002. We apply three tools to solve this mathematical-physical model. First, we find the solitary wave solutions including the trigonometric traveling wave solutions, bell and kink shape solitons using the F -expansion and Improve F -expansion method. We also obtain the soliton solution, singular soliton solutions, rational function solution and elliptic integral function solutions, with the help of the extended trial equation method.